2021
DOI: 10.2478/popets-2021-0050
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Privacy in Digitalization – Analyzing Perspectives of German Farmers

Abstract: Technological progress can disrupt domains and change the way we work and collaborate. This paper presents a qualitative study with 52 German farmers that investigates the impact of the ongoing digitalization process in agriculture and discusses the implications for privacy research. As in other domains, the introduction of digital tools and services leads to the data itself becoming a resource. Sharing this data with products along the supply chain is favored by retailers and consumers, who benefit from trace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…Surprisingly, such risks were neither mentioned by the farmers themselves nor present in the literature. We see the first reason for this missing awareness in the lack of extensive implementation, possibly due to risk aversion in the adoption of new technologies (Marra et al 2003 ), data protection concerns (Linsner et al 2021 ), or the partly unreliable mobile data connection in Germany, especially in rural areas (Fig. 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, such risks were neither mentioned by the farmers themselves nor present in the literature. We see the first reason for this missing awareness in the lack of extensive implementation, possibly due to risk aversion in the adoption of new technologies (Marra et al 2003 ), data protection concerns (Linsner et al 2021 ), or the partly unreliable mobile data connection in Germany, especially in rural areas (Fig. 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The entire process, which comprised the creation of an interview guideline, recruitment of participants, conducting the focus groups, and data analysis and storage, followed the guidelines of the ethical commission of the Technical University of Darmstadt. Some results of these focus groups have already been published in a scientific journal (Linsner et al 2021 ); however, the data were analyzed with a different scope and purpose.…”
Section: Qualitative Analysismentioning
confidence: 99%
“…Lack of IT knowledge The end‐users (eg, farmers) should not be treated as IT experts with knowledge about specifics of IT security 24,27,31 as well as IoT specifics 21 . Facing an heavy workload, the farmers' time budgets are limited 32,33 . Therefore, agricultural IoT solutions need to be ready to use without difficult and time‐consuming manual steps. Sensing and acting Devices used in IoT scenarios are both sensors and actuators.…”
Section: Specifics Of Iot In Wide Area Applicationsmentioning
confidence: 99%
“…21 Facing an heavy workload, the farmers' time budgets are limited. 32,33 Therefore, agricultural IoT solutions need to be ready to use without difficult and time-consuming manual steps. (d) Sensing and acting Devices used in IoT scenarios are both sensors and actuators.…”
Section: Specifics Of Wide Area Iot By the Example Of Agricultural Ap...mentioning
confidence: 99%
“…Various studies have found that privacy plays an important role in decision-making about digital tools and interacting with online technology in a broad range of applications [11,29,47]. Ray et al [40] study privacy concerns among adults of two different age groups, finding that older adults are more concerned about global privacy threats.…”
Section: Related Workmentioning
confidence: 99%